Perancangan Dan Implementasi Caesar Chiper Untuk Meningkatkan Keamanan Sistem Informasi Akademik Sekolah Berbasis Android - Alif Azhar Amsyari; Bayu Gunawan; Rizky Hamdani; Sri Panca Rani; Nita Syahputri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research focuses on the design and implementation of the Caesar Cipher method to improve the security of an Android-based School Academic Information System. In this digital era, data security is a major concern, especially in school academic information systems that manage important data. The Caesar Cipher method, as a simple and easy to implement encryption technique, is used in this research. The research results show that the implementation of Caesar Cipher has succeeded in increasing data security in the system. While this method does not provide a very high level of security, it can be part of a more complex security approach. Overall, this research shows that the design and implementation of Caesar Cipher is an effective step in improving the security of Android-based school academic information systems.